ASPECTOS TÉCNICOS E ECONÔMICOS DA UTILIZAÇÃO DOS CONTROLADORES FACTS NA OPERAÇÃO DOS SISTEMAS DE ENERGIA ELÉTRICA - Cárdenas, Sergio León Escalante (2005)
This work presents the economical and technical aspects of FACTS (flexible ac transmission systems) controllers in steady-state operation of electric power systems (EPS). There Controllers are used in EPS to increase the power transfer limit in the transmission lines and to improve the electromechanical and voltage stability. The models considered in this research are: SVC, TCSC, STATCOM, SSSC and UPFC. The modeling of HVDC link including a commutation capacitor for converter (CCC) is also presented. A Newton-Raphson power flow computer program was implemented in order to assess the steady-state operation of FACTS Controllers. On the other hand, for economic assessment of FACTS application, an optimal power flow (OPF) based on interior point method was implemented and prospectively an OPF using genetic algorithms has been proposed. The studied FACTS Controllers were applied to the IEEE 30 bus and IEEE 118 bus test systems, and a configuration of a real power system regarding to the Brazilian National Interconnected System (SIN) represented with 2256 buses. The analysis of the results obtained from the tests indicates that the operation of a EPS with FACTS is more flexible and presents advantages, such as: lines power transfer increase, possibility of power flow reversal in the lines, a better voltage control in remote buses and operation costs lowering, keeping operation restrictions and fixing both, bus voltages and transmission line power flows.